CLINICAL ASPECTS OF THE LIVER MICROSOMAL CYTOCHROME P-450 SYSTEM FUNCTIONING - Padalko, V.I.; Sevastyanova, T.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In the present review modern representations about cytochrome P-450 system  and  roles of its major multiple forms in an organism are generalized. Drugs induction or inhibition of this system are discussed. Important for clinic  interactions of drugs with P-450 enzymes  are given and practical ways of prevention or minimization of negative consequences of interactions of medical products are discussed.